An enhanced curvature-constrained design method for manufacturable variable stiffness composite laminates. (1st October 2020) - Hong, Zhi; Peeters, Daniël; Turteltaub, Sergio
Highlights: An indirect curvature control method for variable stiffness laminates is developed. A new method for angle retrieval from the optimal lamination parameters is proposed. Two curvature control strategies are compared systematically with the existing one. The proposed hybrid control method provides the best manufacturable designs. Abstract: In this paper, design strategies are developed to explore better approaches of enforcing local layer-wise curvature constraints in the optimization of variable stiffness laminates in order to ensure the manufacturability of optimized designs based on the limitations of automated fiber placement. The methods developed here aim to improve an existing approach of imposing the curvature constraint directly on the fiber angles (i.e., direct control method) and are suitable for a design framework that uses lamination parameters as primary design variables. One approach developed here, termed the indirect control method, enforces the curvature constraint indirectly with better computational efficiency through the spatial gradient of the lamination parameters. It is shown that the curvature constraint on the actual fiber angles can also be satisfied with a sufficiently stringent upper bound albeit it produces overly conservative designs. Alternatively, an enhanced approach, termed the hybrid control method, is developed by combining the direct method and a relaxed version of the indirect control method. The case studies of minimum compliance design indicate that it provides the best manufacturable design among the three methods in the context of variable stiffness laminates using lamination parameters.